DIAGNOSTIC ACCURACY OF MENTZER INDEX AS A SCREENING TOOL FOR THE DIAGNOSIS OF IRON DEFICIENCY ANEMIA BY TAKING IRON PROFILE AS GOLD STANDARD IN PATIENTS PRESENTING WITH HYPOCHROMIC MICROCYTIC ANEMIA AT TERTIARY CARE HOSPITAL, KARACHI - IQBAL , S; AMIN , W; ARSHAD , S; NOORULAIN, . (Biological and Clinical Sciences Research Journal, 2024)
Anemia is the most prevalent haematological condition in newborns and children. A deficiency of iron necessary for synthesizing haemoglobin causes it. This study used the iron profile as the gold standard for patients with hypochromic microcytic anemia at a tertiary care hospital in Karachi to assess the Mentzer index's diagnostic accuracy for iron-deficient anemia. From January 2021 to December 2022, a cross-sectional descriptive study was conducted in the Department of Pediatrics, NICH, Karachi. With the patient's explicit consent, data was prospectively collected. Those who satisfied the diagnostic requirements totaled 163 patients. While frequency and percentages were used to represent qualitative factors, simple descriptive statistics with mean and standard deviation were used to convey quantitative data. The following metrics were calculated: diagnostic accuracy, sensitivity, specificity, positive and negative predictive values, and a significance level set at p-value ≤0.05. A total of 163 patients with hypochromic microcytic anemia were included in the study; their mean age was 8.23±3.57 years. 78 (47.9 percent) and 85 (52.1 percent) were female. For the diagnosis of iron deficiency anemia, the Mentzer index's sensitivity, specificity, positive predictive value, negative predictive value, and diagnostic accuracy were determined to be, respectively, 90.1 percent, 90.1 percent, 93.8 percent, 84.6 percent, and 90.8 percent. According to the study's findings, cell-count-based indices—in particular, the Mentzer index—are trustworthy, widely accessible techniques that have a high degree of discrimination power for identifying iron deficiency anemia.